2007
DOI: 10.1093/cercor/bhm140
|View full text |Cite
|
Sign up to set email alerts
|

Spatio temporal Dynamics of Face Recognition

Abstract: To better understand face recognition, it is necessary to identify not only which brain structures are implicated but also the dynamics of the neuronal activity in these structures. Latencies can then be compared to unravel the temporal dynamics of information processing at the distributed network level. To achieve high spatial and temporal resolution, we used intracerebral recordings in epileptic subjects while they performed a famous/unfamiliar face recognition task. The first components peaked at 110 ms in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
143
3
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(183 citation statements)
references
References 60 publications
36
143
3
1
Order By: Relevance
“…fMRI studies show robust activation during face perception in lateral fusiform gyrus, inferior occipital gyrus, superior temporal cortex, and OFC (Ishai, Schmidt, & Boesiger, 2005;Halgren et al, 1999;Kanwisher et al, 1997). Recordings in patients with implanted electrodes have revealed facerelated activities in posterior and middle fusiform gyri as well as in middle temporal, inferior temporal, and inferior frontal gyri (Barbeau et al, 2008;Allison, Puce, Spencer, & McCarthy, 1999). Agreement between our results and those described in the literature supports the plausibility of N1 generators found in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…fMRI studies show robust activation during face perception in lateral fusiform gyrus, inferior occipital gyrus, superior temporal cortex, and OFC (Ishai, Schmidt, & Boesiger, 2005;Halgren et al, 1999;Kanwisher et al, 1997). Recordings in patients with implanted electrodes have revealed facerelated activities in posterior and middle fusiform gyri as well as in middle temporal, inferior temporal, and inferior frontal gyri (Barbeau et al, 2008;Allison, Puce, Spencer, & McCarthy, 1999). Agreement between our results and those described in the literature supports the plausibility of N1 generators found in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…To identify ERPs generated focally in this region, criteria were polarity reversal between adjacent contacts ( Fig. 1) and/or steep voltage gradients and high voltage fluctuations between adjacent contacts (Fernandez et al, 1999;Barbeau et al, 2008). ERPs in this region had a specific morphology at similar latencies ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Intracranial EEG recordings have shown that faces elicit responses across a number of regions in the ventral temporal visual-processing pathway (Allison et al 1994;Barbeau et al 2008) and furthermore that faces can induce changes in the coherence of broadband (4-45 Hz) power between those regions (Klopp et al 1999;Klopp et al 2000). However, little is known about the functional relevance of this coherence or, in particular, the role of nonlinear (between-frequency) coupling.…”
Section: Discussionmentioning
confidence: 99%